i>Pseudosyllides balearica n.sp.: un nuevo syllido (poliquetos: errantes) del Mar Mediterraneo - Sanartín, M.; G (Cahiers de Biologie Marine, 1982)
A new species, Pseudosyllides balearica n.sp. (Polychaeta: Syllidae) has been discovered from Spanish Mediterranean coasts (Balearic Islands). The description is given. Notes on genus Pseudosyllides and a comparative table between P. balearica and P. curacaoensis are included in this paper.
Kristian Fauchald's Polychaeta DB